Tourism Awareness and Sapta Pesona Training for the Community of the Purus Beach Tourism Area, Padang City - Rika Despica; Elvi Zuriyani (Asian Journal of Community Services, 2022)
Purus Beach is a beach located in the western part of Padang City which has a fairly sloping coast, the beach is really beautiful, the sand area is quite wide and wide (about 30-50 m from the main road to the sea) with a smooth and soft texture, suitable for playing areas. This beach is always crowded with visitors, especially in the afternoon, visitors generally take advantage of the high tide in the afternoon to surf or play speed boats. Every weekend and holiday there are many residents around the city, but this beach has problems that are always hit by the same problems, namely this tourist area has illegal parking problems, security from enforcers, but this is a community service team providing solutions to the community in the object area. This tour is to provide education to the public about the importance of maintaining SAPTA PESONA in the tourist area by providing education to the public and forming a Tourism Awareness Group (POKDARWIS) in the Purus beach tourism area, this is able to provide understanding to the community to maintain this tourist attraction so that it remains a Destination Area Local Tourism and Outside the Province of West Sumatra.